Investigation of Fluoride Release Patterns of Glass Ionomer Lining Materials: A Comparative Study of Chemical, Resin Modified, and Single-Component Glass Ionomer Cements - Neda Sadeghian Marnani; Mehrdad Kazemian (Nanochemistry Research)
Glass ionomer cements have gained widespread acceptance in clinical practice due to advancements in their formulation. This study aimed to investigate the fluoride release patterns of three glass ionomer lining materials: a chemical glass ionomer, Vitrebond (a resin-modified glass ionomer), and Ionoseal (a single-component ready-to-use glass ionomer). Samples of each material were prepared according to the manufacturer’s instructions and immersed in deionized water. Fluoride release was measured at various time points using a fluoride electrode and ion analyzer. Statistical analysis was performed to assess differences in fluoride release among materials and time points. The results revealed significant differences in fluoride release among the different materials and time points. Vitrebond exhibited the highest cumulative fluoride release during the first week, followed by Fuji I and Ionoseal. This trend persisted until the 21st day. All three materials showed a gradual decrease in fluoride release over time, with statistically significant declines observed at each time point. Despite the decline, the level of fluoride release from all materials was deemed sufficient for caries prevention in tooth tissue. Therefore, any of these materials could be considered for clinical use depending on specific circumstances. Future studies should focus on evaluating the ease of use and other favorable properties of these materials to ensure successful clinical applications.